Lawan tetap lawan : kisah perjuangan rakyat menegakkan keadilan - Strategic Info Research Development (Petaling Jaya : Strategic Info Research Development, 2000)
People movement on human rights issues in Malaysia; collection of articles.
In Malay
Keywords: Human rights -- Malaysia; Civil rights -- Malaysia; Malaysia -- Politics and government